Electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery having the same
By using the positive electrode active material layer of layered structural compound particles, the problem of prone to rupture of the positive electrode active material in the prior art is solved, high output characteristics and durability are achieved, and it is suitable for non-aqueous electrolyte secondary batteries.
Patent Information
- Application Number
- CN202210169521.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-11-08
- Filing Date
- 2017-11-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2037-11-02
AI Technical Summary
The positive electrode active substance of the conventional non-aqueous electrolyte secondary battery is prone to rupture during press forming or charging and discharge, resulting in poor output characteristics and difficulty in improving durability.
The positive electrode active material layer consisting of layered structural compound particles formed of two or more transition metals has an average particle size of between 1 and 7 μm, a void ratio of between 10% and 45%, and a density of between 2.7 and 3.9 g/cm3. These characteristics ensure that the positive electrode active material layer does not break during the high density process, thereby improving the output characteristics.
It achieves higher output characteristics and durability than the positive electrode active material composed of traditional secondary particles, ensuring high performance of the non-aqueous electrolyte secondary battery.
Smart Images

Figure CN114520307B_ABST
Abstract
Description
[0001] This application is a divisional application of the application number: 201780068497.2, PCT application number: PCT / JP2017 / 039698, application date: 2017.11.2, invention name: "Electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery having the same". Technical Field
[0002] The present invention relates to an electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery having the same. Background Art
[0003] In the past, as a large-scale power equipment such as electric vehicles, a non-aqueous electrolyte secondary battery positive electrode active material with high output characteristics was required. In order to obtain high output characteristics, it is effective to reduce the number of primary particles in the secondary particles constituting the positive electrode active material or to use a single particle formed by monodispersing the primary particles to constitute the positive electrode active material.
[0004] However, if the positive electrode active material is cracked due to pressure treatment during electrode formation or expansion and contraction during charge and discharge, high output characteristics cannot be obtained. Therefore, various technologies for improving the durability of positive electrode active materials have been proposed.
[0005] For example, a density of 3.5 g / cm 3 A non-aqueous secondary battery having a positive electrode active material with a high density and a porosity of 25% or less (see Patent Document 1). According to this non-aqueous secondary battery, by allowing a large number of voids in the positive electrode, the collector can be prevented from breaking despite the high density, thereby obtaining high output characteristics.
[0006] In addition, for example, a secondary battery positive electrode having a porosity of 30% to 50% and a pore size of 0.09 to 0.30 μm has been proposed (see Patent Document 2). According to this secondary battery positive electrode, the electrode density can be improved by setting the porosity and pore size in appropriate ranges, thereby improving output characteristics.
[0007] In addition, for example, a secondary battery having a positive electrode active material in which the ratio of the volume of pores with a pore diameter of 0.01 to less than 0.1 μm to the volume of pores with a pore diameter of 0.1 to 1.0 μm is 0.3 or less is proposed (see Patent Document 3). According to this secondary battery, the output characteristics can be improved by making the pore distribution within a suitable range.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2009-48876
[0011] Patent Document 2: Japanese Patent Application Publication No. 2010-15904
[0012] Patent Document 3: Japanese Patent Application Publication No. 2012-209161 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, the techniques of Patent Documents 1 to 3 all use secondary particles. In practice, during the compression molding of the positive electrode, the secondary particles constituting the positive electrode active material collapse, which reduces the hole diameter and increases the resistance, resulting in failure to obtain high output characteristics. In particular, if the positive electrode active material breaks, the electrolyte is oxidized and decomposed on the newly generated surface to form a thick SEI, resulting in failure to obtain high output characteristics.
[0015] The present invention has been made in view of the above problems, and an object of the present invention is to provide an electrode for a nonaqueous electrolyte secondary battery capable of obtaining high output characteristics and a nonaqueous electrolyte secondary battery having the same.
[0016] Solutions to Solve Problems
[0017] In order to achieve the above-mentioned purpose, the present invention provides an electrode for a non-aqueous electrolyte secondary battery, which is an electrode for a non-aqueous electrolyte secondary battery having a collector and a positive electrode active material layer arranged on the above-mentioned collector and containing a positive electrode active material, wherein the above-mentioned positive electrode active material contains compound particles having a layered structure formed by two or more transition metals, and the average particle size DSEM of the compound particles based on electron microscope observation is 1 to 7 μm, and the ratio of the 50% particle size D50 in the cumulative particle size distribution based on the volume basis to the above-mentioned average particle size DSEM (D50 / DSEM) is 1 to 4, and the ratio of the 90% particle size D90 in the cumulative particle size distribution based on the volume basis to the 10% particle size D10 in the cumulative particle size distribution based on the volume basis (D90 / D10) is less than 4, and the porosity of the above-mentioned positive electrode active material layer is 10% to 45%.
[0018] The density of the positive electrode active material layer is preferably 2.7 to 3.9 g / cm 3 As a result, higher output characteristics are obtained. In the secondary particles, cracks occur due to pressing, and the parts not coated with the auxiliary agent are exposed to the surface. If it is a single particle, there is no cracking at all, so the output characteristics are relatively high.
[0019] The peak diameter of holes in the hole distribution curve of the positive electrode active material layer is preferably 0.06 to 0.3 μm.
[0020] The average diameter of the holes in the positive electrode active material layer is preferably 0.03 to 0.2 μm.
[0021] The ratio of the peak diameter of the holes in the positive electrode active material layer to the average diameter of the holes (peak diameter / average diameter) is preferably 1.1 to 2.4.
[0022] The positive electrode active material preferably contains Ni, Mn or Al as a main component.
[0023] The present invention provides a nonaqueous electrolyte secondary battery comprising the above-mentioned electrode for a nonaqueous electrolyte secondary battery.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide an electrode for a nonaqueous electrolyte secondary battery capable of obtaining higher output characteristics than before, and a nonaqueous electrolyte secondary battery including the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram showing an example of a hole distribution curve of the positive electrode active material according to the present embodiment.
[0027] Figure 2 This is a diagram showing an example of a hole distribution curve of a positive electrode active material composed of conventional secondary particles.
[0028] Figure 3 This is a diagram showing the relationship between DSEM and D50 / DSEM of the positive electrode active material according to the present embodiment.
[0029] Figure 4 This is a SEM image of the positive electrode active material according to this embodiment.
[0030] Figure 5 This is a SEM image of a positive electrode active material composed of conventional secondary particles.
[0031] Figure 6 This is a graph showing the relationship between the porosity and output of the positive electrode active material layer in Examples and Comparative Examples.
[0032] Figure 7 This is a graph showing the relationship between the density of the positive electrode active material layer and the output in Examples and Comparative Examples.
[0033] Figure 8 This is a diagram showing the relationship between the peak diameter of holes and the output in the hole distribution curves of the positive electrode active material layers of Examples and Comparative Examples.
[0034] Fig. 9 This is a graph showing the relationship between the average diameter of holes in the positive electrode active material layer and the output in Examples and Comparative Examples.
[0035] Fig.10 This is a graph showing the relationship between the peak diameter / average diameter of holes and the output of the positive electrode active materials of Examples and Comparative Examples. DETAILED DESCRIPTION
[0036] One embodiment of the present invention is described in detail with reference to the accompanying drawings. However, the present invention is not limited to the following embodiments. In addition, in this specification, when there are multiple substances belonging to each component in the composition, unless otherwise specified, the content of each component refers to the total amount of the multiple substances present in the composition.
[0037] [Electrodes for non-aqueous electrolyte secondary batteries]
[0038] The electrode for a non-aqueous electrolyte secondary battery involved in the present embodiment has a current collector and an electrode active material layer disposed on the current collector and including an active material layer. The electrode for a non-aqueous electrolyte secondary battery involved in the present embodiment is preferably used as a positive electrode of a non-aqueous electrolyte secondary battery, and is particularly preferably used as a positive electrode of a lithium-ion secondary battery. Therefore, below, the non-aqueous electrolyte secondary battery positive electrode using the electrode for a non-aqueous electrolyte secondary battery involved in the present embodiment as a positive electrode of a lithium-ion secondary battery is described in detail.
[0039] The positive electrode for a nonaqueous electrolyte secondary battery according to the present embodiment includes a current collector and a positive electrode active material layer disposed on the current collector and containing a positive electrode active material.
[0040] As the current collector, for example, aluminum, nickel, stainless steel or the like can be used.
[0041] The positive electrode active material layer includes a positive electrode active material, a conductive auxiliary agent, a binder, and the like.
[0042] The porosity of the positive electrode active material layer involved in this embodiment is 10% to 45%. As described later, the positive electrode active material layer involved in this embodiment is composed of a positive electrode active material containing a single particle. Therefore, in order to obtain higher output characteristics on the basis of fully ensuring a large channel (pathway) for lithium ion diffusion, the positive electrode active material layer is densified. Even if the porosity is reduced to the range of 10% to 45%, the positive electrode active material layer will not be broken. That is, the following situation will not occur as in the previous positive electrode active material containing secondary particles: rupture due to high density, so that the part not coated (attached) by the conductive auxiliary agent is resurfaced (new surface is generated); according to this embodiment, since it is composed of a single particle whose entire surface is coated with a conductive auxiliary agent, high output characteristics are obtained. A more preferred porosity is 20% to 35%.
[0043] Here, the porosity in this embodiment can be measured by mercury intrusion porosimetry. Alternatively, the porosity can be adjusted by adjusting the particle size of the positive electrode active material or by adjusting the pressurization conditions in the method for producing the positive electrode active material layer described later.
[0044] The density of the positive electrode active material layer according to this embodiment is preferably 2.7 to 3.9 g / cm 3 As described above, the positive electrode active material layer according to the present embodiment is composed of single-particle positive electrode active material. Therefore, even if the positive electrode active material layer is densified to 2.7 to 3.9 g / cm 3 The range of can also limit the porosity to the range of 10% to 45%, so that the positive electrode active material layer will not be broken. That is, unlike the previous positive electrode active material containing secondary particles, the following situation will not occur: rupture due to high density, so that the part not covered (attached) by the conductive auxiliary agent is resurfaced (a new surface is generated); according to this embodiment, since it is composed of a single particle whose entire surface is covered with a conductive auxiliary agent, high output characteristics are obtained. The more preferred density is 3.0 to 3.6 g / cm 3 .
[0045] Here, the density in this embodiment can be measured using a density measuring device. In addition, the density can be adjusted by adjusting the particle size of the positive electrode active material or adjusting the pressurization conditions in the method for producing the positive electrode active material layer described later.
[0046] The peak diameter of the holes in the hole distribution curve (pore distribution curve) of the positive electrode active material layer involved in this embodiment is preferably 0.06 to 0.3 μm. If the peak diameter of the holes in the positive electrode active material layer is within this range, the high output characteristics as described above can be obtained more reliably. The more preferred peak diameter of the holes is 0.12 to 0.25 μm.
[0047] The peak diameter of the pores in this embodiment refers to the diameter D of the pores that are the maximum values in the pore distribution curve obtained by the mercury intrusion method in the same manner as the porosity measurement described above, more specifically, the log differential pore volume distribution (dV / dlogD). The log differential pore volume distribution (dV / dlogD) is a curve obtained by dividing the differential pore volume dV by the logarithmic differential value dlogD of the pore diameter and plotting the value against the average pore diameter.
[0048] Here, Figure 1 : is a diagram showing an example of a hole distribution (log differential pore volume distribution) curve of the positive electrode active material involved in this embodiment. Figure 2This is a diagram showing an example of a hole distribution (log differential pore volume distribution) curve of a conventional positive electrode active material composed of secondary particles. Figure 1 and Figure 2 In the figure, the horizontal axis represents the pore diameter D (μm), and the vertical axis represents the log differential pore volume distribution (dV / dlogD). In each figure, three examples are represented by a solid line, a dotted line, and a dashed line.
[0049] As is clear from these figures, a sharp peak is confirmed in the present embodiment using the positive electrode active material including single particles, whereas a broad peak is confirmed in the conventional embodiment using the positive electrode active material including secondary particles.
[0050] The average diameter of the holes in the positive electrode active material layer of the present embodiment is preferably 0.03 to 0.2 μm. If the average diameter of the holes in the positive electrode active material layer is within this range, the high output characteristics described above can be obtained more reliably. The more preferred average diameter of the holes is 0.05 to 0.18 μm. It should be noted that the average diameter of the holes is obtained by measuring the mercury intrusion method based on the same measurement conditions as the above-mentioned porosity measurement.
[0051] In addition, the ratio of the peak diameter of the above-mentioned holes to the average diameter of the above-mentioned holes in the positive electrode active material layer involved in this embodiment (peak diameter / average diameter) is preferably 1.1 to 2.4. If the ratio of the peak diameter of the holes to the average diameter of the holes (peak diameter / average diameter) is within this range, the high output characteristics as described above can be obtained more reliably. A more preferred ratio of the peak diameter of the holes to the average diameter of the holes (peak diameter / average diameter) is 1.1 to 1.8.
[0052] By using a positive electrode active material including single particles as in the present embodiment, the value of peak diameter / average diameter is reduced to fall within the above range. Therefore, the gaps between particles will not become too small, and the electrolyte can penetrate the entire body, thereby obtaining high output characteristics.
[0053] The positive electrode active material layer is formed by applying a positive electrode mixture on a current collector, followed by drying and pressurizing. The positive electrode mixture is obtained by mixing a positive electrode active material, a conductive auxiliary agent, a binder, etc., with a solvent.
[0054] As the conductive auxiliary agent, for example, natural graphite, artificial graphite, acetylene black, etc. can be used.
[0055] As the binder, for example, polyvinylidene fluoride, polytetrafluoroethylene, polyamide acrylic resin, etc. can be used.
[0056] Next, the positive electrode active material will be described in detail.
[0057] The positive electrode active material involved in this embodiment comprises compound particles having a layered structure formed by two or more transition metals, wherein the average particle size DSEM of the compound particles based on electron microscope observation is 1 to 7 μm, the ratio of the 50% particle size D50 in the cumulative particle size distribution based on the volume basis to the above-mentioned average particle size DSEM (D50 / DSEM) is 1 to 4, and the ratio of the 90% particle size D90 in the cumulative particle size distribution based on the volume basis to the 10% particle size D10 in the cumulative particle size distribution based on the volume basis (D90 / D10) is less than 4.
[0058] The compound particles having a layered structure formed of two or more transition metals preferably contain Ni, Mn or Al as a main component. Among them, lithium transition metal composite oxide particles (hereinafter also referred to as "composite oxide particles") having a layered structure containing Ni are preferably used.
[0059] DSEM of 1 to 7 μm and D50 / DSEM of 1 to 4 means that the composite oxide particles constituting the positive electrode active material are single particles consisting of a single particle or particles consisting of a small number of primary particles. That is, in this embodiment, all particles are single particles or particles consisting of a small number of primary particles are collectively referred to as "single particles". It should be noted that the ratio of single particle active material of the positive electrode active material involved in this embodiment is preferably 80% or more.
[0060] Here, Figure 3 DSEM and D50 / DSEM of the positive electrode active material according to the present embodiment are shown in FIG. Figure 3 In the figure, the horizontal axis represents DSEM (μm) and the vertical axis represents D50 / DSEM. Figure 3 The region surrounded by the dotted line is a region where DSEM is 1 to 7 μm and D50 / DSEM is 1 to 4, which is a region of single particles defined in this embodiment. Compared with secondary particles formed by aggregation of primary particles, single particles located in the above region have fewer contact grain boundaries between primary particles.
[0061] Figure 4 This is a SEM image of the positive electrode active material according to this embodiment. Figure 5 This is a SEM image of a conventional positive electrode active material composed of secondary particles. Figure 4 As shown, in the single particles constituting the positive electrode active material according to the present embodiment, the particles do not aggregate, so the conductive additive can cover (attach) the entire surface of each particle. Therefore, the conductive additive can be used efficiently and the output characteristics can be improved. In contrast, in Figure 5In the secondary particles constituting the conventional positive electrode active material, the primary particles aggregate to form the secondary particles, so the conductive auxiliary agent cannot enter the gaps between the primary particles, and the conductive auxiliary agent cannot cover (attach) the entire surface of the primary particles. Therefore, the conductive auxiliary agent cannot be used efficiently, and the output characteristics cannot be improved.
[0062] In addition, D90 / D10 being 4 or less means that the distribution width in the cumulative particle size distribution based on the volume basis of the composite oxide particles is narrow and the particle size is uniform. By having such a feature, high durability is obtained, and as a result, high output characteristics are obtained.
[0063] Here, compared with the positive electrode active material comprising lithium transition metal composite oxide particles composed of secondary particles formed by a large number of primary particles, the positive electrode active material comprising lithium transition metal composite oxide particles composed of conventional single particles can suppress the decrease in capacity retention rate and the increase in the diffusion and migration resistance of lithium ions caused by the disconnection of the lithium ion conductive path based on the grain boundary dissociation of the secondary particles during the charge and discharge cycle, thereby showing excellent durability.
[0064] On the other hand, a three-dimensional grain boundary network such as that of the positive electrode active material composed of aggregated particles is hardly formed, and a high output design utilizing grain boundary conduction cannot be performed, so there is a tendency to make the output characteristics insufficient. In order to improve the output characteristics, it is considered to improve by reducing the particle size (DSEM) of a single particle, but if it is too small, there is a tendency that the interaction between the powders increases, the deterioration of the plate filling becomes significant, and sometimes the operability is significantly deteriorated due to the reduction in powder fluidity. On the other hand, it can be considered that: in order to obtain a practical energy density, a certain degree of particle size is required, but when the particle size is increased, there is a tendency to make the insufficient output more significant.
[0065] Compared with previous single particles, the particle size of the lithium transition metal composite oxide particles involved in this embodiment is more consistent. Therefore, it can be considered that even when charging and discharging at a high current density, the unevenness of the charge and discharge depth of each particle caused by the current concentration on a part of the particles can be suppressed, thereby suppressing the increase in resistance caused by current concentration and suppressing local degradation caused by cycling.
[0066] By further making the particle size of lithium transition metal composite oxide particles with few grain boundaries uniform, the particles will not collapse even when pressed under high pressure when making the electrode, so it is believed that the gaps between the particles can be uniform. It is also believed that: in the case of forming a battery, the gaps between the particles are filled with electrolytes and become diffusion paths for lithium ions. By making the size of the diffusion path uniform, the uneven charging and discharging of each particle can be suppressed. It is therefore believed that: even lithium transition metal composite oxide particles with few contact grain boundaries between primary particles can guarantee the filling of the plate and achieve excellent output characteristics.
[0067] In addition, in general, in the case of synthesizing single particles, in order to make the particles grow, the heat treatment temperature needs to be high temperature. In particular, if high-temperature sintering is performed in a composition with a high Ni ratio, the Ni element is sometimes mixed into the Li site, so-called disordering. Disordering will hinder the diffusion of Li ions in the composite oxide particles and form resistance, resulting in reduced charge and discharge capacity and reduced output characteristics at practical current density, so it is preferably suppressed. By suppressing disordering, it is possible to achieve better capacity and output characteristics in a single particle.
[0068] In the composite oxide particles constituting the positive electrode active material, from the viewpoint of durability, the average particle size DSEM based on electron microscope observation is 1 to 7 μm. In addition, from the viewpoint of output density and plate filling, when the range of x described later is 0.3≤x<0.6, it is preferably 1.1 μm or more, more preferably 1.3 μm or more, and preferably 4 μm or less, more preferably 2 μm or less. When the range of x is 0.6≤x≤0.95, it is preferably 1.1 μm or more, more preferably 1.3 μm or more, and preferably 5 μm or less, more preferably 4 μm or less.
[0069] As for the average particle size DSEM based on electron microscope observation, a scanning electron microscope (SEM) is used to observe in the range of 1000 to 10000 times according to the particle size, 100 particles whose outlines can be confirmed are selected, and the spherical conversion diameter of the selected particles is calculated using image processing software, and the arithmetic mean of the obtained spherical conversion diameters is obtained.
[0070] The ratio D50 / DSEM of the 50% particle size D50 in the cumulative particle size distribution based on the volume basis of the composite oxide particles to the average particle size DSEM based on electron microscope observation is 1 to 4. When D50 / DSEM is 1, it means that all particles are single particles, and the closer to 1, the smaller the number of primary particles. From the viewpoint of durability, D50 / DSEM is preferably 1 or more and less than 4, and from the viewpoint of output density, D50 / DSEM is preferably 3 or less, and particularly preferably 2.5 or less.
[0071] The 50% particle size D50 of the composite oxide particles is, for example, 1 to 21 μm, preferably 1.5 μm or more, more preferably 3 μm or more, and preferably 8 μm or less, more preferably 5.5 μm or less from the viewpoint of output density.
[0072] The 50% particle size D50 is obtained as a particle size corresponding to 50% of the cumulative particle size distribution from the small diameter side in the volume-based cumulative particle size distribution measured under wet conditions using a laser diffraction particle size distribution measuring device. Similarly, the 90% particle size D90 and 10% particle size D10 described later are obtained as particle sizes corresponding to 90% and 10% of the cumulative particle size from the small diameter side, respectively.
[0073] The ratio of the 90% particle size D90 to the 10% particle size D10 in the volume-based cumulative particle size distribution of the composite oxide particles indicates the breadth of the particle size distribution, and the smaller the value, the more uniform the particle size. D90 / D10 is 4 or less, preferably 3 or less, and more preferably 2.5 or less from the viewpoint of output density. The lower limit of D90 / D10 is, for example, 1.2 or more.
[0074] The lithium transition metal composite oxide has a layered structure containing Ni in its composition. Examples of such lithium transition metal composite oxides include lithium nickel composite oxides and lithium nickel cobalt manganese composite oxides. Among them, the lithium transition metal composite oxide preferably has a composition represented by the following formula (1).
[0075] [Chemistry 1]
[0076] LipNixCoyM 1 zO2+α···Formula (1)
[0077] [In formula (1), p, x, y, z and α satisfy 1.0≤p≤1.3, 0.3≤x≤0.95, 0≤y≤0.4, 0≤z≤0.5, x+y+z=1, −0.1≤α≤0.1, and M1 represents at least one of Mn and Al.]
[0078] The lithium transition metal composite oxide particles may be doped with elements other than the elements constituting the lithium transition metal composite oxide. As the doped elements, for example, B, Na, Mg, Si, P, S, K, Ca, Ti, V, Cr, Zn, Sr, Y, Zr, Nb, Mo, In, Sn, Ba, La, Ce, Nd, Sm, Eu, Gd, Ta, W and Bi can be cited. Among them, Mg, Ti, and W can be preferably exemplified. As compounds used for doping of these elements, oxides and fluorides containing at least one element selected from these elements, and Li composite oxides thereof, etc. can be cited. The doping amount, for example, can be 0.005 mol% or more and 10 mol% or less relative to the lithium transition metal composite oxide particles.
[0079] In addition, the lithium transition metal composite oxide particles can be composite oxide particles having core particles containing lithium transition metal composite oxides and attachments disposed on the surface of the core particles. The attachments can be disposed on at least a portion of the surface of the core particles, preferably on an area of more than 1% of the surface area of the core particles. The composition of the attachments can be appropriately selected according to the purpose, and examples thereof include oxides and fluorides of at least one element selected from B, Na, Mg, Si, P, S, K, Ca, Ti, V, Cr, Zn, Sr, Y, Zr, Nb, Mo, In, Sn, Ba, La, Ce, Nd, Sm, Eu, Gd, Ta, W and Bi, and Li composite oxides thereof. The content of the attachments can be, for example, 0.03% by mass or more and 10% by mass or less in the lithium transition metal composite oxide particles, preferably 0.1% by mass or more and 2% by mass or less.
[0080] The composition of the lithium transition metal composite oxide contains Ni. From the perspective of the initial efficiency of the non-aqueous electrolyte secondary battery, the disorder of the Ni element obtained by the X-ray diffraction method of the lithium transition metal composite oxide is preferably 4.0% or less, more preferably 2.0% or less, and further preferably 1.5% or less. Here, the disorder of the Ni element refers to the chemical disorder of the transition metal ions (Ni ions) that should occupy the original site. In the layered lithium transition metal composite oxide, when expressed in Wyckoff symbols, the representative is the replacement of the lithium ions that should occupy the site shown in 3b (3b site, the same below) and the transition metal ions that should occupy the 3a site. The smaller the disorder of the Ni element, the higher the initial efficiency, so it is preferred.
[0081] The disorder of the Ni element in the lithium transition metal composite oxide can be obtained by X-ray diffraction. For the lithium transition metal composite oxide, the X-ray diffraction spectrum is measured by CuKα rays. The composition model is set to Li1-dNidMeO2 (Me is a transition metal other than Ni in the lithium transition metal composite oxide), and the structure is optimized by Rietveld analysis based on the obtained X-ray diffraction spectrum. The percentage of d calculated as a result of the structural optimization is set to the value of the disorder of the Ni element.
[0082] In the case where the lithium transition metal composite oxide has a composition shown in formula (1), in one embodiment of the present invention, the range of a, the range of particle sizes shown in DSEM, D50, D90 and D10, and the more preferred range of disorder of the Ni element are sometimes changed corresponding to the value of x in formula (1), and they are exemplified below.
[0083] In the formula (1), when x satisfies 0.3≤x<0.8, D50 / DSEM is preferably 1 or more and 2 or less from the viewpoint of output density.
[0084] In the formula (1), when x satisfies 0.3≤x<0.6, it is preferable to satisfy at least one of the following conditions from the viewpoint of output density.
[0085] (i) From the viewpoint of charge and discharge capacity, the disorder of the Ni element in the lithium transition metal composite oxide particles, as determined by an x-ray diffraction method, is preferably 1.5% or less.
[0086] (ii) D90 / D10 is preferably 3.0 or less, more preferably 2.5 or less.
[0087] (iii) From the viewpoint of electrode plate filling properties, D50 is preferably 1 μm or more and 5.5 μm or less, and more preferably 1 μm or more and 3 μm or less.
[0088] (iv) In the formula (1), a preferably satisfies 1.1<a<1.2.
[0089] In the formula (1), when x satisfies 0.6≤x<0.8, it is preferable to satisfy at least one of the following aspects from the viewpoint of output density.
[0090] (i) From the viewpoint of charge and discharge capacity, the disorder of the Ni element in the lithium transition metal composite oxide particles, as determined by an x-ray diffraction method, is preferably 2.0% or less.
[0091] (ii) D90 / D10 is preferably 2.3 or less.
[0092] (iii) From the viewpoint of electrode plate filling properties, D50 is preferably 1 μm or more and 5.5 μm or less.
[0093] In the formula (1), when x satisfies 0.8≤x<0.95, it is preferred that at least one of the following aspects is satisfied from the viewpoint of output density.
[0094] (i) From the viewpoint of charge and discharge capacity, the disorder of the Ni element in the lithium transition metal composite oxide particles, as determined by an x-ray diffraction method, is preferably 4.0% or less.
[0095] (ii) D90 / D10 is preferably 3.0 or less.
[0096] (iii) From the viewpoint of electrode plate filling properties, D50 is preferably 1 μm or more and 5.5 μm or less.
[0097] The lithium transition metal composite oxide particles contained in the positive electrode active material according to the present embodiment can be produced by a production method comprising the following steps: mixing a lithium compound and an oxide having a desired composition to obtain a raw material mixture; and heat treating the obtained raw material mixture. The heat-treated product obtained after the heat treatment can be crushed, or can be washed with water to remove unreacted substances, by-products, etc. In addition, it can also be further dispersed, classified, etc.
[0098] Methods for obtaining oxides having a desired composition include: a method in which raw material compounds (hydroxides, carbonate compounds, etc.) are mixed according to a target composition and decomposed into oxides by heat treatment; a co-precipitation method in which a raw material compound soluble in a solvent is dissolved in a solvent, and a precursor is precipitated by temperature adjustment, pH adjustment, addition of a complexing agent, etc. according to the target composition, and these precursors are heat treated to obtain an oxide.
[0099] Hereinafter, an example of a method for producing a positive electrode active material will be described by taking the case where a lithium transition metal composite oxide is represented by formula (1) as an example.
[0100] The method for obtaining the raw material mixture preferably includes: obtaining a composite oxide containing Ni, Co and at least one selected from Mn and Al by a coprecipitation method; and mixing the obtained composite oxide with a lithium compound such as lithium carbonate or lithium hydroxide.
[0101] The method for obtaining a composite oxide by coprecipitation may include: a seed generation step, in which the pH of a mixed aqueous solution containing metal ions is adjusted to a desired composition to obtain a seed; a crystallization step, in which the generated seed grows to obtain a composite hydroxide having desired characteristics; and a step of heat-treating the obtained composite hydroxide to obtain a composite oxide. For details of the method for obtaining a composite oxide, reference may be made to Japanese Patent Application Publication No. 2003-292322, Japanese Patent Application Publication No. 2011-116580, etc.
[0102] The composite oxide obtained by the coprecipitation method has a particle size distribution index D90 / D10 of, for example, 3 or less, preferably 2 or less. Also, D50 is, for example, 12 μm or less, preferably 6 μm or less, more preferably 4 μm or less, and, for example, 1 μm or more, preferably 2 μm or more.
[0103] The content ratio of Ni, Co, Mn, and Al in the composite oxide may be, for example, 1 / 1 / 1, 6 / 2 / 2, or 8 / 1 / 1.
[0104] The raw material mixture preferably further comprises a lithium compound on the basis of the composite oxide. Examples of the lithium compound include lithium carbonate, lithium hydroxide, lithium oxide, and the like. The particle size of the lithium compound used is, for example, 0.1 to 100 μm, preferably 2 to 20 μm, in terms of D50. The lithium content in the raw material mixture is, for example, Li / (Ni+Co+Mn+Al) and is 1.0 or more, and can be 1.3 or less, preferably 1.2 or less. The mixing of the composite oxide and the lithium compound can be carried out, for example, using a high-speed shear mixer or the like.
[0105] The obtained raw material mixture is subjected to heat treatment to obtain lithium transition metal composite oxide particles. The temperature of the heat treatment is, for example, 700°C to 1100°C. The heat treatment may be performed at a single temperature or at multiple temperatures. When the heat treatment is performed at multiple temperatures, for example, the first heat treatment may be performed at a temperature in the range of 700 to 925°C, followed by a second heat treatment at a temperature in the range of 930 to 1100°C. A third heat treatment may also be performed at a temperature in the range of 700 to 850°C.
[0106] The heat treatment time is, for example, 1 to 40 hours. When the heat treatment is performed at a plurality of temperatures, each of the temperatures may be 1 to 10 hours. The heat treatment atmosphere may be air or oxygen atmosphere.
[0107] The heat-treated product may be subjected to a crushing treatment, a dispersion treatment, a classification treatment, etc. In this way, the desired lithium-transition metal composite oxide particles can be obtained.
[0108] In addition, after the heat-treated product is subjected to crushing treatment, dispersion treatment, classification treatment, etc., a lithium compound may be further mixed to obtain a mixture, and then additional heat treatment may be performed. In the case of further mixing a lithium compound, the lithium content in the mixture may be, for example, 1.05 to 1.3, preferably 1.1 to 1.2, in terms of Li / (Ni+Co+Mn+Al). In addition, the temperature of the additional heat treatment may be in the range of 850 to 1000°C, preferably in the range of 870 to 950°C, preferably a temperature lower than the heat treatment temperature of the raw material mixture. The heat treatment time of the additional heat treatment may be, for example, 2 to 15 hours. Crushing treatment, dispersion treatment, classification treatment, etc. may also be performed after the additional heat treatment.
[0109] [Non-aqueous electrolyte secondary battery]
[0110] The nonaqueous electrolyte secondary battery of the present embodiment has the above-mentioned nonaqueous electrolyte secondary battery electrode as a positive electrode. In addition, the nonaqueous electrolyte secondary battery of the present embodiment is configured to include a nonaqueous electrolyte, a separator, etc. on the basis of having a conventionally known nonaqueous electrolyte secondary battery negative electrode as a negative electrode.
[0111] Regarding the negative electrode, non-aqueous electrolyte, separator, etc. for non-aqueous electrolyte secondary batteries, for example, the negative electrode, non-aqueous electrolyte, separator, etc. for non-aqueous electrolyte secondary batteries described in Japanese Patent Publication No. 2002-075367, Japanese Patent Publication No. 2011-146390, Japanese Patent Publication No. 2006-12433, etc. can be appropriately adopted, and the manufacturing method thereof can also use the manufacturing method described in these publications.
[0112] It should be noted that the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope that can achieve the object of the present invention are included in the present invention.
[0113] Example
[0114] Next, examples of the present invention will be described. However, the present invention is not limited to the following examples.
[0115] <Production Example 1 of Positive Electrode Active Material>
[0116] (Seed Crystal Generation Process)
[0117] First, in the reaction tank, 10 kg of water was added and stirred while adjusting the ammonium ion concentration to 1.8% by mass. The temperature in the tank was set to 25° C., nitrogen was circulated, and the oxygen concentration in the reaction tank space was maintained at 10% by volume or less. A 25% by mass sodium hydroxide aqueous solution was added to the water in the reaction tank to adjust the pH value of the solution in the tank to 13.5 or more.
[0118] Next, the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were mixed to prepare a mixed aqueous solution with a molar ratio of 1:1:1.
[0119] The mixed aqueous solution was added until the amount of the solute reached 4 mol, and seed crystals were generated while the pH of the reaction solution was controlled to 12.0 or more with a sodium hydroxide solution.
[0120] (Crystallization process)
[0121] After the above-mentioned seed generation step, the temperature in the tank is maintained at 25°C or above until the crystallization step is completed. In addition, a mixed aqueous solution of 1200 moles of solute is prepared, and it is added together with an aqueous ammonia solution, while maintaining the ammonium ion concentration in the solution at 2000ppm or above, while adding it simultaneously for more than 5 hours in a manner that does not cause new seed generation in the reaction tank. In the reaction, sodium hydroxide solution is used to control the pH value in the reaction solution to be maintained at 10.5 to 12.0. Sampling is performed successively during the reaction, and the addition is terminated when the D50 of the composite hydroxide particles becomes about 4.5μm.
[0122] The product was then washed with water, filtered, and dried to obtain composite hydroxide particles. The obtained hydroxide precursor was heat treated at 300° C. for 20 hours in an air atmosphere to obtain a composite oxide having a composition ratio of Ni / Co / Mn=0.33 / 0.33 / 0.33, D10=3.4 μm, D50=4.5 μm, D90=6.0 μm, and D90 / D10=1.8.
[0123] (Synthesis process)
[0124] The obtained composite oxide and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.15 to obtain a raw material mixture. The obtained raw material mixture is calcined at 925°C for 7.5 hours in the atmosphere, and then calcined at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body is crushed, dispersed for 10 minutes using a resin ball mill, and passed through a dry sieve to obtain a powder. The obtained powder is classified into three parts, large, medium and small, using a dry classifier, and the medium particles are separated. The proportion of medium particles after classification is 46wt% relative to that before classification.
[0125] In summary, the average particle size DSEM based on electron microscope observation is 3.6μm, D10=3.7μm, D50=5.1μm, D90=6.7μm, the ratio of D50 to the average particle size DSEM D50 / DSEM is 1.4, the ratio D90 / D10 in the particle size distribution is 1.8, the Ni disorder amount is 0.3%, and the composition formula is: Li 1.15 Ni 0.33 Co0.33 Mn 0.33 The lithium transition metal composite oxide particles are shown as O2.
[0126] <Production Example 2 of Positive Electrode Active Material>
[0127] The operation was carried out under the same conditions, except that the timing of ending the addition of the mixed aqueous solution in the crystallization step of Manufacturing Example 1 was changed to when the D50 of the composite hydroxide particles became about 3.0 μm, to obtain a composite oxide having a composition ratio of Ni / Co / Mn=0.33 / 0.33 / 0.33, D10=2.2 μm, D50=3.0 μm, D90=4.1 μm, and D90 / D10=1.9.
[0128] The obtained composite oxide and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The obtained raw material mixture is calcined at 925°C in the air for 7.5 hours, and then calcined at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body is crushed, dispersed in a resin ball mill for 30 minutes, and passed through a dry sieve to obtain a powder. The obtained powder and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.17, and calcined in the air at 900°C for 10 hours to obtain a sintered body. The obtained sintered body is crushed, dispersed in a resin ball mill for 30 minutes, and passed through a dry sieve to obtain a powder.
[0129] In summary, the average particle size DSEM is 1.2μm, D10=1.5μm, D50=3.3μm, D90=5.1μm, the ratio of D50 to the average particle size DSEM D50 / DSEM is 2.8, the D90 / D10 ratio in the particle size distribution is 3.4, the Ni disorder amount is 0.9%, and the composition formula is: Li 1.17 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles are shown as O2.
[0130] <Production Example 3 of Positive Electrode Active Material>
[0131] A composite oxide is obtained under the same conditions as in Manufacturing Example 2. The composite oxide obtained and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The raw material mixture obtained is calcined at 925°C in the atmosphere for 7.5 hours, and then calcined at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body is crushed, dispersed for 30 minutes using a resin ball mill, and passed through a dry sieve to obtain a powder. The obtained powder and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.17, and calcined at 900°C in the atmosphere for 10 hours to obtain a sintered body. The obtained sintered body is crushed, and a jet mill is used to adjust the supply pressure to 0.4 MPa and the crushing pressure to 0.55 MPa without crushing the primary particles, and a secondary dispersion treatment is performed, and a powder is obtained by passing through a dry sieve.
[0132] In summary, the average particle size DSEM is 1.4 μm, D10 = 1.1 μm, D50 = 1.9 μm, D90 = 2.8 μm, the ratio of D50 to the average particle size DSEM D50 / DSEM is 1.4, the D90 / D10 ratio in the particle size distribution is 2.5, the Ni disorder amount is 1.0%, and the composition formula is: Li 1.17 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles are shown as O2.
[0133] <Production Example 4 of Positive Electrode Active Material>
[0134] A composite oxide is obtained under the same conditions as in Production Example 2. The composite oxide obtained and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.05 to obtain a raw material mixture. The raw material mixture obtained is calcined at 925°C in the atmosphere for 7.5 hours, and then calcined at 1030°C for 6 hours to obtain a sintered body. The obtained sintered body is crushed, dispersed for 10 minutes using a resin ball mill, and passed through a dry sieve to obtain a powder. The obtained powder and lithium carbonate are mixed in such a manner that Li / (Ni+Co+Mn)=1.14, and calcined at 900°C in the atmosphere for 10 hours to obtain a sintered body. The obtained sintered body is crushed, dispersed for 10 minutes using a resin ball mill, and passed through a dry sieve to obtain a powder.
[0135] In summary, the average particle size DSEM is 1.25 μm, D10 = 2.7 μm, D50 = 4.5 μm, D90 = 6.7 μm, the ratio of D50 to the average particle size DSEM of the primary particles is 3.6, the D90 / D10 ratio in the particle size distribution is 2.5, the Ni disorder amount is 1.0%, and the composition formula is: Li 1.14 Ni 0.33Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles are shown as O2.
[0136] <Production Example 5 of Positive Electrode Active Material>
[0137] A composite oxide was obtained under the same conditions as in Production Example 2. The composite oxide obtained and lithium carbonate were mixed so that Li / (Ni+Co+Mn)=1.15 to obtain a raw material mixture. The obtained raw material mixture was calcined at 950°C for 15 hours in the atmosphere to obtain a sintered body. The obtained sintered body was crushed, dispersed for 10 minutes using a resin ball mill, and passed through a dry sieve to obtain a powder.
[0138] In summary, the average particle size DSEM is 0.49 μm, D10 = 3.0 μm, D50 = 4.4 μm, D90 = 7.6 μm, the ratio of D50 to the average particle size DSEM D50 / DSEM is 9.0, the D90 / D10 ratio in the particle size distribution is 2.5, the Ni disorder amount is 0.9%, and the composition formula is: Li 1.15 Ni 0.33 Co 0.33 Mn 0.33 The lithium transition metal composite oxide particles are shown as O2.
[0139] <Production Example 6 of Positive Electrode Active Material>
[0140] The mixed aqueous solution was obtained by changing the mixing ratio of the nickel sulfate solution, the cobalt sulfate solution and the manganese sulfate solution in the manufacturing example 1 to 8:1:1 in terms of molar ratio, and changing the timing of ending the introduction of the mixed aqueous solution in the crystallization step to when the D50 of the composite hydroxide particles becomes 3.2 μm. The same conditions were used to obtain a composite hydroxide having a composition ratio of Ni / Co / Mn=0.80 / 0.10 / 0.10 and D 10 =2.2μm, D 50 =2.9μm, D 90 =4.0μm, D 90 / D 10=1.8 composite oxide. The obtained composite oxide and lithium hydroxide monohydrate are mixed in such a manner that Li / (Ni+Co+Mn)=1.04 to obtain a raw material mixture. The obtained raw material mixture is calcined at 780°C for 5 hours in an oxygen flow, calcined at 900°C for 10 hours, and then calcined at 780°C for 5 hours to obtain a sintered body. The obtained sintered body is crushed and dispersed in a resin ball mill for 10 minutes to obtain a powder. The powder and 10% by mass of water relative to the powder are added to a rotary blade high-speed stirring mixer, stirred at 2000 rpm to dissolve the residual alkali at the grain boundary, dispersed, dried at 350°C, and passed through a dry sieve to obtain a powder.
[0141] In summary, the average particle size DSEM is 1.5μm, D10=2.2μm, D50=3.6μm, D90=6.0μm, the ratio of D50 to the average particle size DSEM D50 / DSEM is 2.4, the D90 / D10 ratio in the particle size distribution is 2.7, the Ni disorder amount is 1.6%, and the composition formula is: Li 1.04 Ni 0.80 Co 0.10 Mn 0.10 The lithium transition metal composite oxide particles are shown as O2.
[0142] <Evaluation>
[0143] Using the lithium transition metal composite oxide of each Production Example obtained as described above as a positive electrode active material, an evaluation battery was prepared by the following procedure.
[0144] First, 96 parts by mass of each positive electrode active material obtained as described above, 3 parts by mass of acetylene black and 1 part by mass of polyvinylidene fluoride (PVDF) were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture. The obtained positive electrode mixture was coated on an aluminum foil as a current collector, and after drying, it was compression-molded with a roller press, and then cut into a specified size to make a positive electrode.
[0145] After lead electrodes were attached to the graphite as the positive electrode and the negative electrode obtained as described above, a separator was placed between the positive electrode and the negative electrode, and they were placed in a bag-shaped laminate bag. As the separator, a PE separator with a thickness of 16 μm was used.
[0146] Next, the laminate was dried in vacuum at 65° C. to remove moisture adsorbed on each member. Thereafter, an electrolyte solution was injected into the laminate bag in an argon atmosphere and the bag was sealed.
[0147] The battery thus obtained was placed in a thermostatic chamber at 25°C and aged with a weak current. As an electrolyte, the following electrolyte was used: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4, 1.5% by mass of vinylene carbonate (VC) was added, and then lithium hexafluorophosphate (LiPF6) was dissolved to a concentration of 1.2 mol / l.
[0148] D10, D50 and D90 of each positive electrode active material were measured by using a laser diffraction particle size distribution measuring apparatus (SALD-3100 manufactured by Shimadzu Corporation) to measure the volume-based cumulative particle size distribution, and the respective particle sizes were obtained by accumulating from the smaller diameter side.
[0149] Regarding the DSEM of each positive electrode active material, 100 particles whose outlines could be confirmed were selected from the images obtained by observing with a scanning electron microscope (SEM) at 1000 to 10000 times, and the spherical converted diameters of the selected particles were calculated using image processing software (ImageJ), and the value was obtained as the arithmetic mean of the obtained spherical converted diameters.
[0150] The disorder value of the nickel element (Ni disorder amount) was determined by the following procedure using an X-ray diffraction method.
[0151] The obtained lithium transition metal composite oxide particles were measured for an X-ray diffraction spectrum using CuKα rays. Based on the obtained X-ray diffraction spectrum, the composition model was assumed to be Li 1-d Ni d MeO2 (Me is a transition metal other than nickel in the lithium transition metal composite oxide) was used to optimize the structure of the lithium transition metal composite oxide by Rietveld analysis. The percentage of d calculated as a result of the structural optimization was taken as the Ni disorder amount.
[0152] The porosity, peak diameter of the cavities, and average diameter of the cavities were measured using mercury intrusion porosimetry. The diameter region exceeding about 5 μm was estimated to be noise in the measurement and was cut off. The density was calculated from the electrode weight and electrode volume.
[0153] In addition, the output density of the evaluation battery obtained as described above was evaluated. Specifically, the evaluation battery was discharged, set to a state of SOC50%, and kept at 25°C for 2 hours. Then, a constant current discharge was performed from the state of SOC50%, and the DC resistance at the 10th second was measured to calculate the output density. It should be noted that the lower limit voltage of the discharge was set to 2.7V. The results are shown in Table 1.
[0154] [Table 1]
[0155]
[0156] In addition, the evaluation results are summarized in Figure 6 to Figure 10 middle. Figure 6 This is a graph showing the relationship between the porosity and output of the positive electrode active material layer in the present example and the comparative example. Figure 7 This is a graph showing the relationship between the density of the positive electrode active material layer and the output in the present example and the comparative example. Figure 8 This is a diagram showing the relationship between the peak diameter of holes and the output in the hole distribution curves of the positive electrode active material layers of the present example and the comparative example. Fig. 9 This is a graph showing the relationship between the average diameter of the holes in the positive electrode active material layer and the output in the present example and the comparative example. Fig.10 This is a graph showing the relationship between the peak diameter / average diameter of holes and the output of the positive electrode active materials of the present example and the comparative example.
[0157] As shown in Table 1, it was confirmed that Examples 1 to 29 had higher output densities than Comparative Examples 1 to 12.
[0158] exist Figure 6 In the figure, the horizontal axis represents the void ratio (%) and the vertical axis represents the output (W / kg). Figure 6 It was confirmed that high output characteristics can be obtained by setting the porosity of the positive electrode active material layer to 10% to 45%.
[0159] exist Figure 7 The horizontal axis represents density (g / cm 3 ), the vertical axis represents output (W / kg). Figure 7 It can be confirmed that by setting the density of the positive electrode active material layer to 2.7 to 3.9 g / cm 3 , thus obtaining high output characteristics.
[0160] exist Figure 8 In the figure, the horizontal axis represents the peak diameter (μm) and the vertical axis represents the output (W / kg). Figure 8 It was confirmed that high output characteristics can be obtained by setting the peak diameter of holes in the hole distribution curve to 0.06 to 0.3 μm.
[0161] exist Fig. 9 In the figure, the horizontal axis represents the average diameter (μm) and the vertical axis represents the output (W / kg). Fig. 9 It was confirmed that high output characteristics were obtained by setting the average diameter of the holes to 0.03 to 0.2 μm.
[0162] exist Fig.10 In the figure, the horizontal axis represents the hole peak diameter / hole average diameter, and the vertical axis represents the output (W / kg). Fig.10It was confirmed that high output characteristics were obtained by setting the ratio of the peak diameter of holes to the average diameter of holes (peak diameter / average diameter) to 1.1 to 2.4.
[0163] Industrial Applicability
[0164] A nonaqueous electrolyte secondary battery including an electrode for a nonaqueous electrolyte secondary battery using the positive electrode active material of the present invention has excellent output density and durability, and can therefore be suitably used in large power equipment such as electric vehicles.
Claims
1. An electrode for a non-aqueous electrolyte secondary battery, comprising a current collector and a positive electrode active material layer disposed on the current collector and containing a positive electrode active material, The positive electrode active material comprises compound particles having a layered structure formed of two or more transition metals, and the compound particles are lithium transition metal composite oxide particles represented by the following formula (1): The compound particles have an arithmetic mean particle size DSEM based on electron microscope observation of 1.1 to 7 μm, a ratio D50 / DSEM of a 50% particle size D50 in a volume-based cumulative particle size distribution measured using a laser diffraction particle size distribution measuring apparatus to the arithmetic mean particle size DSEM of 1 to 4, and a ratio D90 / D10 of a 90% particle size D90 in the volume-based cumulative particle size distribution to a 10% particle size D10 in the volume-based cumulative particle size distribution of 4 or less, The peak diameter of the holes in the hole distribution curve of the positive electrode active material layer is 0.12 to 0.25 μm. Li p Ni x Co y M 1 z O 2+α ・・・Formula (1) In formula (1), p, x, y, z and α satisfy 1.0≤p≤1.3, 0.3≤x<0.6, 0≤y≤0.4, 0≤z≤0.5, x+y+z=1, -0.1≤α≤0.1, M 1 represents at least one of Mn and A1.
2. The electrode for a nonaqueous electrolyte secondary battery according to claim 1, wherein The porosity of the positive electrode active material layer is 10 to 45%.
3. The electrode for a nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The density of the positive electrode active material layer is 2.7 to 3.9 g / cm 3 .
4. The electrode for a nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The average diameter of the holes in the positive electrode active material layer is 0.03 to 0.2 μm.
5. The electrode for a non-aqueous electrolyte secondary battery according to claim 4, wherein The ratio of the peak diameter of the holes in the positive electrode active material layer to the average diameter of the holes, ie, peak diameter / average diameter, is 1.1 to 2.
4. 6 . A non-aqueous electrolyte secondary battery comprising the electrode for a non-aqueous electrolyte secondary battery according to claim 1 .
Citation Information
Patent Citations
Positive electrode active material for lithium battery, manufacturing method for the active material, and secondary battery using it
JP2002075367A
Method for manufacturing active substance for positive electrode of lithium ion secondary battery
JP2003292322A
Positive electrode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2006012433A
Nonaqueous secondary battery
JP2009048876A
Nonaqueous electrolyte secondary battery
JP2010015904A